Guidelines for Enhancing Teachers' ICT Competency for Learning Management Based on The ICT Leadership Framework of School Administrators Under The Catholic Education Council of Thailand - Buakharn, Rawiwan; Pheeraphan, Nutteerat; Langka, Wilailak (Saengtham College Journal, 2024)
The objective of this research was to propose guidelines for enhancing teachers' ICT competency for learning management based on the ICT leadership framework of school administrators through interviews with 10 people consisting of experts, school administrators, and teachers. The sample group was selected using the purposive sampling method. The research instrument used was an interview questionnaire on the guidelines for enhancing teachers' ICT competency for learning management based on the ICT leadership framework of school administrators. Data obtained was subsequently analyzed with content analysis. The results of the study has found that the guidelines for enhancing teachers' ICT competency for learning management based on the ICT leadership framework of school administrators can be divided into 6 categories: 1) Vision 2) Learning and Teaching 3) Productivity and Professional Practice 4) Support, Management, and Operations 5) Assessment and Evaluation 6) Social, Legal, and Ethical Issues.